PERSEPSI KOMUNITAS SEKOLAH TENTANG LIBRARY APPS TERHADAP PEMBERDAYAAN PERPUSTAKAAN - Alberto, Achmad Riyadi; Johan, Riche Cynthia; Rullyana, Gema (Universitas Pendidikan Indonesia, 2017)
Abstract. This research is motivated by the development of information and communication technology (ICT) in the library world so rapidly that allows libraries in the present to develop its services into digital-based services. This study aims to find out the school community’s perception of library apps developed by Riche Cynthia Johan, Hana Silvana, and Holin Sulistyo and its influence on library empowerment at the library of SD Laboratorium Percontohan UPI Bandung. Library apps in this research belong to the context of m-libraries, which is a library that meets the needs of its users by using mobile platforms such as smartphones,computers, and other mobile devices. Empowerment of library is the utilization of all aspects of the implementation of libraries to the best in order to achieve the expected goals. An analysis of the schoolcommunity’s perception of library apps using the Technology Acceptance Model (TAM) includes: ease of use, usefulness, usability, usage trends, and real-use conditions. While the empowerment of the library includes aspects: information empowerment, empowerment of learning resources, empowerment of human resources, empowerment of library facilities, and library promotion. The research method used in this research is descriptive method with quantitative approach. Population and sample in this research is school community at SD Laboratorium Percontohan UPI Bandung. Determination of sample criteria by using disproportionate stratified random sampling with the number of samples of 83 respondents. Data analysis using simple linear regression to measure the influence of school community perception about library apps to library empowerment. The result of data analysis shows that there is influence between school community perception about library apps to library empowerment at library of SD Laboratorium Percontohan UPI Bandung which is proved by library acceptance level and library empowerment improvement.